(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2022)
Even the most basic of artificial intelligence (AI) systems can outperform humans in some milestone tasks. The following article will present the study on how AI-based software can be used in medical devices. The medical industry has seen astounding advances in AI is used extensively in medical sciences and many other sectors. AI-based software as a medical device will deliver safe and effective software functionality that improves the quality of care that patient receives. Along with its benefits, it also faces challenges, including the need for regulation to keep up with the pace of technology.